Flour mixture of rice flour, corn and cassava starch in the production of gluten-free white bread - López,Ana Cristina Ballesteros (2004)
The use of rice flour corn and cassava starch was evaluated in several formulations aiming to find a flour mixture to replace wheat flour in the production of free-gluten white bread. Production parameters were evaluated through sensory analysis. The resulting breads were evaluated taking into account physical parameters (crumb appearance, specific volume and moisture) and sensorial parameters (flavor, appearance, crumb texture, crust color and satisfaction). Regarding flavor and moisture, breads prepared with the three different ingredients were not statistically different at 5% probability by the Tuckey test. However, they differed significantly regarding the specific volume, crumb texture, crust color, degree of satisfaction and external appearance. Rice flour bread presented the best parameters, being preferred by the sensory evaluation panel, followed by corn starch bread and cassava starch bread. Breads prepared with rice flour resulted in a softer product, presenting a better consistency with small alveoli homogeneously distributed. As far as crumb texture was concerned, corn starch bread presented larger alveoli, while cassava starch resulted in bread with expandable and gummy crumb, with granulation without alveoli, and undesirable sensorial characteristics. Production parameters were established based on these results and a mixture of flours, composed by 45% rice flour, 35% corn starch and 20% cassava starch presented good results originating bread with crumb formed by uniform and well distributed cells, and pleasant flavor and appearance.